Pengaruh Pemberian Pakan yang Berbeda terhadap Pertumbuhan Tukik Penyu Lekang (Lepidochelys Olivacea) di Turtle Conservation and Education Center Pulau Serangan: Effect of Different Feed Giving on the Growth of Lekang Sea Turtle (Lepidochelys Olivacea) in TCEC Serangan Island - Komang Adi Wika Wiguna; Kadek Yuniari Suryatini; I Wayan Suanda; I Gusti Agung Gede Wiadnyana (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This study was carried out the effect of different feeding on the growth of lekang juveniles (Lepidochelys olivacea) at the Turtle Conservation and Education Center (TCEC), Serangan, Bali. The study was conducted for six weeks using a Completely Randomized Design with 3 treatments, namely P1 (scad mackerel), P2 (vannamei shrimp), and P3 (kepah shells). The treatments were repeated 5 times and each replication repeated 3 times using 45 juveniles. The study was analyzed with analysis of variance. The results showed that there was an effect of different feeding on the growth of lekang juveniles. The highest growth rate of lekang juveniles is found in P1 (scad mackerel) and the lowest growth rate is found in P3 (kepah shells).